North America Drawn from the latest and best Authorities - Kitchin, Thomas, d. 1784; Terry, Garnet fl. 1778-1798 (Harrison, John fl. 1784-1792, 1787)
18th century Copper engraving. Relief shown pictorially. Printed in cartouche in upper left corner: ”North America Drawn from the latest and best Authorities.” Printed within top border on left side: ”Longitude West from London.” Printed beneath bottom border: ”Engraved for Jno. Harrison. No. 115 Newgate Street, Sepr. 29th, 1787.” Printed beneath bottom border on left side: ”T. Kitchin Del.” Printed beneath bottom border on right side: ”Engraved by G. Terry.” Depicts northern California as “New Albion” with a range of mountains called the “Snowy Mountains.” East of New Albion is “Teguayo & Quivira.” The most northwestern areas of North America are left blank with the legend, “These Parts are unknown.” North of New Albion is the “Western Sea” and the “River of the West” running to the Pacific Ocean from “Pikes Lake.” Areas occupied by Native American tribes including the Snake, the Chicasaws, the Mascoutops, the Outaganis, the Eskimo or “Estimeaux,” the Apaches, and the Cherokee or “Cherakees”are indicated. Other regions labeled on the map include “New Mexico,” Louisiana, East and West Florida, Georgia, North Carolina, South Carolina, Virginia, Pennsylvania, Maryland, New York, New England, “Labrador or New Britain”, Hudson’s Bay, and the southern tip of Greenland. Prime Meridian: London. Scale c.a. 1:17,000,000. Thomas Kitichin (1717-1784) was a highly prolific English engraver and publisher. He wrote many books on varied subjects in addition to his cartographic work. He was hydrographer to the King and created maps for and with several renowned publishers including Bowen, Dalrymple, Dunn, Elphinstone, Jefferys, "London Magazine," Luttrell, Mackenzie and Willdey. His works include Elphinstone's "Scotland" (1745), Willdey's "Highlands" (1746), "English Atlas" (1749), maps for "London Magazine" (1760-5), Mitchell's "America" (1755), "England Illustrated" (1764) and "Pocket Atlas" (1769). After Kitchin's death in 1784, his plates passed into the hands of Bowels and Carver (Moreland and Bannister, 170; Tooley, 358; Skelton, 74). Garnet Terry was an engraver and jeweler in London. He worked for Taylor and Skinner (1777-8), Armstrong (1776), Mackenzie (1775), Rapin (1784-9) and Turner (1794). His work also includes "Harrison's Atlas" (1787) and "Map Louth" (1778) (Tooley, 614). John Harrison was a London printer, publisher and engraver. His works include Rapin's "History of England" (1784-9), "Africa" (1787), "School Atlas" (1791), "America after D'Anville" (1791), "English Counties" (1791-2) and "General and Co. Atlas" (1815) (Tooley, 284). This particular map is similar to Sayer's 1786 map, "new map of the whole continent of America divided into north and south and West Indies" (Wheat, 237, entry 210). Source(s): Moreland, Carl and David Bannister. "Antique Maps: A Collector's Handbook." New York: Longman Group, Ltd., 1983. Tooley, Ronald Vere. "Tooley's Dictionary of Mapmakers." Hertfordshire: Map Collector Publications Limited, 1979. Wheat, Carl I. "Mapping the Transmississippi West." Volume 1. San Francisco: Institute of Historical Cartography, 1957.